2018
DOI: 10.3126/jcmsn.v14i2.20217
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Serum Ferritin Level in Female Patient with Alopecia

Abstract: Introduction: Total body iron store is an integral factor in the development of hair follicle. Numerous studies have been done seeking for the relationship between body iron store and various forms of chronic diffuse hair loss, with relatively contradictory findings in various reports in these studies. The main objective of this study is to find out if there is any association between total body iron store and various types of chronic diffuse hair loss in females in reproductive age. Materials and Methods: Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…Globally, in Nepal, 60 female patients of age group 15-50 years with chronic diffuse hair loss with equal number of age-and gender-matched controls were enrolled in hospital based case control study. Patients with AA and androgenetic alopecia had significantly lower serum ferritin than controls [14]. Also in accordance with current study there are two studies by Kantor et al [15] and Esfandiarpour et al [16] who also found mean serum ferritin level to be significantly lower in cases than in control.…”
Section: Discussionsupporting
confidence: 91%
“…Globally, in Nepal, 60 female patients of age group 15-50 years with chronic diffuse hair loss with equal number of age-and gender-matched controls were enrolled in hospital based case control study. Patients with AA and androgenetic alopecia had significantly lower serum ferritin than controls [14]. Also in accordance with current study there are two studies by Kantor et al [15] and Esfandiarpour et al [16] who also found mean serum ferritin level to be significantly lower in cases than in control.…”
Section: Discussionsupporting
confidence: 91%
“…A Nepali study reported mean Hb level in CTE was 10.01±1.33 g/dl. 18 In present study 92.9% females with diffuse hair loss showed lower serum ferritin level (SFL) (<30 ng/ml) with mean SFL 16.3±11.61 ng/ml. Tamer et al found mean SFL of females with chronic diffuse hair loss was 14.72±10.70 ng/ml.…”
Section: Discussionmentioning
confidence: 50%
“…A Nepali study found mean SFL in FPHL was 18.39±9.14 ng/ml. 18 A Bangladeshi study also found significantly lower mean SFL in FPHL with a mean SFL 12.50 ±3.37 ng/ml. 22 In this study, females with chronic diffuse hair loss, 34.3% subjects were in iron deficiency state (SFL<12ng/ml), 34.3% were in iron depletion state (SFL 12-20 ng/ml) and only 2.9% had normal ferritin level (SFL >70 ng/ml).An Indian study found 65% of the subjects were in iron deficient state and 20% of the subjects were in iron depleted state .…”
Section: Discussionmentioning
confidence: 85%
“…When the studies were pooled, a statistically significant difference was seen, with the mean ferritin values lower in patients with alopecia at MD = −18.51 ng/dL (−25.85; −11.16; p < 0.01) with significant heterogeneity among the studies (I 2 = 93%, p < 0.01). When outliers [19,29,33] were excluded from the meta-analysis, a statistically significant difference in ferritin levels was still seen between the patients and controls at MD = −18.23 ng/dL (−22.93; −13.53; p < 0.01, I 2 = 74%, p < 0.01). When the studies were omitted one at a time in the influence analyses, the difference in pooled MD between patients and controls was still statistically significant.…”
Section: Difference In Mean Ferritin Values Between Patients and Cont...mentioning
confidence: 99%
“…When the studies were pooled in the meta-analysis, a statistically significant difference was seen with lower mean ferritin levels in patients with alopecia (MD = −20.65 ng/dL [−29.74; −11.55; p < 0.01]) with significant heterogeneity among the studies (I 2 = 94%, p < 0.01). A statistically significant difference in ferritin levels between the patients and controls was still found when outlier papers [19,29,33] were omitted from the meta-analysis (MD = −21.11 ng/dL [−28.14; −14.08; p < 0.01, I 2 = 80%, p < 0.01]). Omitting study by study in influence analyses still resulted in a statistically significant difference in pooled MD between patients and controls.…”
Section: Difference In Mean Ferritin Levels Between Patients and Cont...mentioning
confidence: 99%